Tariff Policy Challenges for Electronic Transmissions in Indonesia - Naufalia Dinar Primacita; Khoirunurrofik Khoirunurrofik (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This research introduces a novel empirical estimate of potential customs duty revenue from digitally transmitted imports in Indonesia, addressing a gap in digital trade policy research that has been largely filled by conceptual and legal analyses. Research Objectives: This study aims to operationalize digitally transmitted imports using Harmonized System (HS) codes across five subsectors registered in the Indonesian HS: (1)films/movies, (2)printed matter-books, (3)sound & media, (4)software, and (5)video games. Research Methods: This study constructs a panel dataset covering the period 2018–2023, using data from the Ministry of Finance and Central Bureau of Statistics. The analysis employs a two-way fixed-effects panel econometric regression model to control for unobserved heterogeneity across subsectors and over time. Empirical Results: The results indicate a positive relationship between import volume and state revenue from import duties, suggesting that higher import volumes directly contribute to increased fiscal receipts, strengthening the role of import duties. Implications: These findings highlight the growing fiscal relevance of digitally transmitted trade and suggest that the government should accelerate investment in digital infrastructure and strengthen cyber oversight to support sustainable growth in digital trade. JEL Classification: F13, F47, H2